(untitled) (Annals of Medical Research, 2021)
Aim: This report aims to assess the diagnostic utility of Tru-Cut biopsy in the diagnosis of breast mass in patients admitted to our breast unit in our clinic.Material and Methods: Between March 2013 and June 2018, In Ortadogu Private Hospital, Adana, 13.660 participants visited the breast unit and 472 participants of them aged 22-91 years experienced Tru-Cut biopsy(TCB) because of clinical doubt and/ or BI-RADS ( Breast Imaging Reporting and Data System ) III– V categorization. TCB specimens were compared with the histopathological reports of follow-up procedures including surgical procedures. When the pathology document was not compatible with clinical / image uncertainties, a biopsy was performed as a diagnostic method to exclude carcinoma.Results: The histopathological diagnosis of the TCB specimens showed that 237 cases (50.2%) were benign lesions, 219 (46.4%) were malignant lesions and 16 (3.4%) of them were disconcordance. Of the patients who underwent Tru-Cut biopsy, 256 (54.2%) had palpable and 216(45.8%) had nonpalpable lesions. Pathological results were not compatible with clinical / imaging suspicion in 3.4% of cases. TCB exhibited a sensitivity of 95.4%, 100% specificity, PPV of 100%, NPV of 96.1%, and diagnostic accuracy of 97.8%. There were no cases with false positivity.Conclusion: This study shows that Tru-Cut biopsy can safely be applied as a component of triple evaluation of suspected breast lesions. Multidisciplinary teamwork is crucial to implement the Tru-Cut biopsy, which replaces the present surgical approach to treat breast lesion and prevent from diagnostic inaccuracies.Keywords: Tru-Cut Biopsy; Breast Carcinoma; Disconcordance.